Executing Jakarta DKI Province's Regulation Number 4 2015 on Betawi Culture Preservation - Aziz Rahimy; Zeffry Alkatiri; Rozanna Mulyani (Polit Journal Scientific Journal of Politics, 2023)
As globalization evolves, it leads to a gradual erosion of local cultures, including in Indonesia. It's imperative for the government to nurture and enhance Indonesian culture. However, there's a noticeable decline in the cultural preservation efforts by DKI Jakarta's Regional Government, negatively impacting relevant stakeholders. This research delves into how DKI Jakarta's Regional Regulation No. 4 of 2015, focused on the Preservation of Betawi Culture, is being integrated into the educational curriculum. The main objective is to devise strategies for embedding the Betawi language into the local educational content, aiming to safeguard it against the risk of disappearing, aligning with the goals of the 2015 regulation. A notable issue is the differing perceptions between DKI Jakarta’s Culture Service officials and the Education and Community Service Office regarding the significance of researching and promoting the protection of Betawi language and literature, compared to public opinion. The research adopts a descriptive qualitative approach, suitable for analyzing societal phenomena that are not quantifiable, allowing for a detailed depiction of the observations. Literature Review is used as the main method for gathering data. The outcome of this study includes practical solutions for integrating the Betawi language into the local educational content, thereby contributing to its preservation and averting the danger of its extinction.